Pengaruh Pajanan Radiasi Sinar-X dari Radiografi Panoramik terhadap pH Saliva (The Effects of Panoramic Dental X-Ray Radiation Exposure on Salivary pH) - Nungky Tias Susanti; Swasthi Prasetyarini; Amandia Dewi Permana Shita (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Background: Panoramic radiograph is a dental radiodiagnosis which is often used to assist in establishing diagnosis and determining treatment plans using low dose x-ray radiation exposure.The basic working principle of panoramic radiograph is using ionizing radiation which causes ionization reactions on the affected objects. Radiation area in patients undergoing panoramic radiograph involves salivary glands, thus it generates certain impacts in the quality and quantity of saliva produced. Aim: To analyze the effects of panoramic dental x-ray radiation exposure on salivary pH. Research Method: This study used quasi experimental research method with pre and post test only control group design. Eight people were chosen as samples based on inclusion and exclusion criteria. Saliva testing was performed to the chosen samples pre and post panoramic dental x-ray radiation exposure. The research data were measured using paired t-test statistical analysis. Result: There wassignificant difference on salivary pH pre and post panoramic dental x-ray radiation exposure (p<0,05). Conclusion: Panoramic dental x-ray exposure can decrease salivary pH. Keywords: Panoramic radiograph, Salivary pH